Complexity of gastroschisis predicts outcome: epidemiology and experience in an Australian tertiary centre - Sarah J. Melov; Irene Tsang; Ralph Cohen; Nadia Badawi; Karen Walker; Soundappan S. V. Soundappan; Thushari I. Alahakoon (BMC, 2018)
Abstract Background Gastroschisis is a congenital anomaly of the fetal abdominal wall, usually to the right side of umbilical insertion. It is often detected by routine antenatal ultrasound. Significant maternal and pediatric resources are utilised in the care of women and infants with gastroschisis. Increasing rates of gastroschisis worldwide have led institutions to review local data and investigate outcomes. A collaborative project was developed to review local epidemiology and investigate antenatal and neonatal factors influencing hospital length of stay (LOS) and total parental nutrition (TPN) in infants born with gastroschisis. Methods We performed a five-year review of infants born with gastroschisis (2011-2015) at a major Australian centre. Complex gastroschisis was defined as involvement of stenosis, atresia, ischemia, volvulus or perforation and closed or vanishing gastroschisis. We extracted data from files and databases at the two participating hospitals, a major maternal fetal medicine centre and the affiliated children's hospital. Results There were 56 infants antenatally diagnosed with gastroschisis with no terminations, one stillbirth (2%) and one infant with 'vanishing' gastroschisis. The mean maternal age was 23.9 years (range, 15-39 years). The mean gestation at delivery was 36 weeks (range, 25-39+ 3 weeks). Of the 55 neonates who received surgical management, 62% had primary closure. The median LOS was 33 (IQR, 23-45) days and the median duration of TPN was 26 (IQR, 17-36) days. Longer days on TPN (median 35 vs 16 days, P = 0.03) was associated with antenatal finding of multiple dilated bowel loops. Postnatal diagnosis of complex gastroschisis was made in 16% of cases and was associated with both longer LOS (median 89 vs 30 days, P = 0.003) and days on TPN (median 46 vs 21 days, P = 0.009). Conclusion Complex gastroschisis was associated with greater days on TPN and LOS. We found no late-gestation stillbirths and a low overall rate of 1.8%, suggesting the risk for stillbirth associated with gastroschisis is lower than previously documented. This information may assist counselling families. Improved data collection worldwide may reveal causative factors and enable antenatal outcome predictors.